Comment on "A Model for Bonanza Gold Deposits" By S.B. Romberger - Wilson, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1993)
Summary Romberger's (1992) paper suggests that deposition of 500 tonnes of gold in six unusually rich Nevada deposits was dueto normal ore-bearing solutions flowing at a more rapid rate and for a longer period of time than usual through well-developed channels perpetuated by continual brecciation. It is now understood that plate tectonics requires that 15million years ago the Yellowstone mantle plume should have formed and begun to migrate eastward relative to the North American plate at a rate of approximately 35 km per million years. This paper proposes that the passage of the plume past the deposits coincided with the time of ore deposition, indicating that the plume was a factor in forming the ore bodies. It mentions some other reasons why plumes should be taken into account in economic geology.